PELATIHAN PENINGKATAN KAPASITAS IBU-IBU PKK DAN KADER POSYANDU SEBAGAI AGEN LITERASI KEUANGAN KELUARGA SEJAHTERA DI DESA KARYAMEKAR, PASIRWANGI, KAB. GARUT JAWA BARAT - Wardhani Indah Sari; Wiwin Suhada; Rika Ristiawati; Iis Basyiroh; Ifah Masrifah (JURNAL ABDIMAS PLJ, 2025)
This Community Service Program (PKM) aims to enhance the capacity of PKK members and Posyandu cadres as financial literacy agents for family welfare in Karyamekar Village, Pasirwangi District, Garut, West Java. The training was conducted on November 14–15, 2025, in Classroom 1 of SDN Karyamekar 2 and attended by 25 participants from PKK and Posyandu groups. The program was carried out in collaboration with the Karyamekar Village Office as the community partner. The training methods included interactive lectures, group discussions, family financial planning simulations, and mentoring in basic financial recording. The results show an improvement in participants’ understanding of financial literacy concepts, their ability to prepare family budgets, and their readiness to provide financial education to the community. This activity is expected to strengthen the role of PKK members and Posyandu cadres in supporting family economic resilience in Karyamekar Village.